2019
DOI: 10.1111/eth.12874
|View full text |Cite
|
Sign up to set email alerts
|

Scatter‐hoarding and cache pilfering of rodents in response to seed abundance

Abstract: Seed caching and reciprocal cache pilferage play an important role in the coexistence of food‐hoarding animals. Understanding what affects seed caching and how cache pilferage occurs is an important question in seed dispersal ecology. However, tracking seed fate and cache pilferage presents substantial practical difficulties. Siberian chipmunks Tamias sibiricus always remove the entire pericarp when scatter‐hoarding acorns of Mongolian oak Quercus mongolica, whereas wood mice Apodemus peninsulae often store wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Too few acorns were cached in our forest floor survival experiment to assess how treatments affected cache recovery. However, cache recovery based on spatial memory may display different trends than cache pilferage, as the two are driven by fundamentally different behavioral processes (Wang et al 2018, Yi et al 2019. We found higher overall survival of artificial caches (24%) than rodent caches (15.7%), consistent with a recovery advantage for cache owners (Steele et al 2011).…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Too few acorns were cached in our forest floor survival experiment to assess how treatments affected cache recovery. However, cache recovery based on spatial memory may display different trends than cache pilferage, as the two are driven by fundamentally different behavioral processes (Wang et al 2018, Yi et al 2019. We found higher overall survival of artificial caches (24%) than rodent caches (15.7%), consistent with a recovery advantage for cache owners (Steele et al 2011).…”
Section: Discussionmentioning
confidence: 51%
“…, Yi et al. ). We found higher overall survival of artificial caches (24%) than rodent caches (15.7%), consistent with a recovery advantage for cache owners (Steele et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One species of squirrel that does not perform embryo excision of early germinating acorns appears to have overcome this problem with a suite of other behavioral strategies that allow it to manage the challenge of early germination (Table 2). Although this species is known to larderhoard food for winter hibernation, the relatively solitary species also regularly engages in scatterhoarding and, as a result, contributes significantly to seed dispersal (Wang et al, 2018;Yi et al, 2019b). In China, Siberian chipmunks (T. sibiricus) exhibit the unique behavior of pericarp removal of acorns of Q. mongolica, Q. variabilis, Q. aliena and Q. serrata var.…”
Section: Behavioral Adaptation Of Siberian Chipmunks To Early Germinating Oaksmentioning
confidence: 99%
“…Moreover, field evidence showed that whole acorns cached by wood mice, Apodemus peninsulae, were more likely to be pilfered by Siberian chipmunks than acorns that had pericarps removed. Pilferage rates of whole intact acorns were estimated at 28% during both periods of both high and low seed abundance (Yi et al, 2019b).…”
Section: Behavioral Adaptation Of Siberian Chipmunks To Early Germinating Oaksmentioning
confidence: 99%